Asymptotic formula for the sum of eigenvalues of fourth order differential operator on Banach space - Baksia, Ozlem; Sezer, Yonca (UNIV NIS, FAC SCI MATH, 2024)
In this paper, we derive a trace formula for self adjoint fourth order differential operator with bounded operator coefficient in the separable Banach space. Compared with the regularized trace problems studied in Hilbert space, the fact that the asymptotic formulas obtained are on Banach space is an important result of the theoretical setting which we considered.
Keywords: Separable Banach space; trace class operator; spectrum; dense embedding; 2ND REGULARIZED TRACE; SPECTRAL THEORY; Mathematics